2007
DOI: 10.1039/b701582h
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalysed methanol carbonylation in the presence of bis(ditertiarybutylphosphinomethyl)benzene

Abstract: Catalysts prepared in situ from 1,2-(Bu t 2 PCH 2 ) 2 C 6 H 4 (DTBPMB) and [RhCl(CO) 2 ] 2 catalyse the carbonylation of methanol in the presence of MeI at rates (4.12 and 8.90 × 10 −4 mol dm −3 s −1 at 150 and 180 • C respectively) faster than those in the absence of added phosphine, although they decompose to [RhI 2 (CO) 2 ] − over time. HPIR studies suggest that MeI adds to [Rh(DTBPMB)X(CO)] (X = Cl or I), which have been isolated and fully characterised, to give [Rh(DTBPMB)MeI 2 (CO)]. [Rh(DTBPMB)MeI 2 (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The 31 P NMR spectrum (CDCl 3 , see Supporting Information Figure S20) of [(BPX)Rh(CO)Cl] consisted of two doublets of doublets at 51.5 ppm ( 1 J Rh−P = 173.7 Hz, 2 J P−P = 32.6 Hz, trans to Cl) and 13.9 ppm ( 1 J Rh−P = 127.0 Hz, 2 J P−P = 32.1 Hz, trans to CO), which is similar to the 31 P NMR spectrum of [(DTBPX)Rh-(CO)Cl], although in the latter case the respective one-bond Rh−P coupling constants are slightly smaller at 170.8 and 123.2 Hz, respectively. 32 Previous studies have shown correlations between the magnitude of the one-bond Rh−P coupling constants and the σ-donation of the trans influencing ligand. 33 It is thought that coupling constants of a given metal and ligand are a good indicator of the relative s characters of the orbitals involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The 31 P NMR spectrum (CDCl 3 , see Supporting Information Figure S20) of [(BPX)Rh(CO)Cl] consisted of two doublets of doublets at 51.5 ppm ( 1 J Rh−P = 173.7 Hz, 2 J P−P = 32.6 Hz, trans to Cl) and 13.9 ppm ( 1 J Rh−P = 127.0 Hz, 2 J P−P = 32.1 Hz, trans to CO), which is similar to the 31 P NMR spectrum of [(DTBPX)Rh-(CO)Cl], although in the latter case the respective one-bond Rh−P coupling constants are slightly smaller at 170.8 and 123.2 Hz, respectively. 32 Previous studies have shown correlations between the magnitude of the one-bond Rh−P coupling constants and the σ-donation of the trans influencing ligand. 33 It is thought that coupling constants of a given metal and ligand are a good indicator of the relative s characters of the orbitals involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Another prominent approach to achieve an isomerizing functionalization is isomerizing alkoxycarbonylation. 142,143 This reaction, first observed for fatty acid esters by Cole-Hamilton and co-workers, 144 converts the internal double bond deep in the hydrocarbon chain very selectively to a terminal ester group by reaction with carbon monoxide and methanol. The reaction is promoted by Pd(II) catalysts with bulky electron-rich diphosphine ligands, like 1,2-bis[(di-tert-butylphosphino)methyl]benzene (dtbpx).…”
Section: Isomerization Functionalizationmentioning
confidence: 99%
“…171 The process of methanol carbonylation is traditionally carried out with cis-[Rh(CO) 2 I 2 ] -in the Monsanto process. 102 The authors showed that a catalytic system based on [RhCl(CO) 2 ] 2 /DTBPMB, with added methyl iodide, gives higher initial rates for the reaction than the Monsanto catalyst at 150-180℃.…”
Section: Other Reactions Involving Rhodiummentioning
confidence: 99%